Crowdfunding for musicians - Webber, Laser Malena (Berklle Press, 2019)
You will learn to: Choose a crowfunding site that supports your needs, whether it is to support a specific prokect (e.g., Kickstarter) or your ongoing carrer (e.g., Patreon). Develop your fan base and mobilize them to support your projects. Structure reward levels that inspire fan participation -without creating too much work for yourself! -- Promote your campaign throught social media and effective press strategies.